Remote Sensing-Based Study for Evaluating the Changes in Glacial Area: A Case Study from Himachal Pradesh, India - Rai P.K.; Mishra V.N.; Singh S.; Prasad R.; Nathawat M.S. (My University, 2025)
Purpose: Glaciers influence a variety of natural systems in the environment and act as a key source of freshwater worldwide. Remote sensing satellite data has proved to be important tool for defining the glacier inventory and retreating pattern of a glacial region. Methods: An attempt has been made to investigate changes in glacial area of five selected glaciers i.e. Bara shigri, Chota shigri, Hamtah, G4 and Parvati glacier in Himanchal Pradesh from 1976 to 2013 through the LANDSAT data of MSS (1976), TM (1989 and 2009), ETM+ (2001) and OLI-TIRS (2013) whereas ASTER-DEM data was used for relief information. Glacier snout positions were demarcated by identifying glacier features such as the origin of the stream from the terminus, supraglacial lakes, and disposition of end moraines. The uncertainty (U) was calculated for multi-temporal measures of the glacier front position using these images. Results: Amongst the selected five glaciers in which snout could be demarcated accurately for all the datasets, three glaciers experienced very nominal retreat of their terminus; the maximum retreat (6.63 m) was calculated in the case of G4 glacier while Humtah glacier exhibited advancement in 37 years. However, Bara shigri glacier experienced a retreat of 1.50 m. The study shows that the glacial covered area reduced from 154.58 to 123.39 km2 indicating 20.17% deglaciation during the period from 1976 to 2013. Conclusion: The outcome of this study may obligatory to monitor spatio-temporal changes in glaciers and their conservation towards the sustainable management of water resources in Himalayan river watersheds. © 2017, Springer International Publishing Switzerland.